The Impact of Project-Based Learning on Elementary Students’ Creative Thinking and Science Achievement: A Quasi-Experimental Study - Amri Zulkarnain; Hartini Haritani; Marhamah Marhamah (IJE : Interdisciplinary Journal of Education, 2026)
This study examines the impact of Project-Based Learning (PjBL) on elementary students’ creative thinking skills and science achievement. Although previous research has widely explored PjBL at the secondary level, limited empirical evidence exists at the elementary level, particularly using multivariate statistical approaches. This study employed a quantitative quasi-experimental design with a one-way MANOVA. A total of 40 third-grade students were selected using cluster random sampling and divided into an experimental group (n = 20) and a control group (n = 20). Data were collected using a validated creative thinking rubric and a multiple-choice science achievement test. The results revealed a significant multivariate effect of instructional model on the combined dependent variables, Wilks’ Λ = 0.72, F (2, 37) = 7.18, p < .01, η² = 0.28. Univariate analysis indicated that PjBL significantly improved creative thinking skills (p = 0.011) and science achievement (p = 0.006). These findings demonstrate that PjBL is an effective instructional approach for enhancing both cognitive and creative competencies in elementary education. The study contributes to constructivist learning literature and highlights the importance of innovative pedagogical strategies in fostering 21st-century skills.